Serious Game For Raising Awareness In Protecting Malaysia Native Wildlife (Born) - Kerk, Zhi Yuan (2023)
Over the past few decades, extinction of wildlife is increasing and their challenges to survive in wildlife have emerged. Malaysia's focus is often taken away by today’s hot topic and doesn’t aware of topics that will not be covered by the media. One of the topics is the Malaysia Native Wildlife extinction problem. They are facing threats in their habitat and facing challenges to live in our land. Deforestation is a major problem that causes Malaysia Native Wildlife to lose their habitat. The forest is being cut down to make space for plantations such as palm oil and other crops. Logging and farming activities have decimated Malaysia’s forest cover, resulting in significant environmental deterioration. For example, the Orang Utan population has dropped by 40% in the last 20 years because of deforestation and one of the rare Malaysia native species, the Malayan Flying Lemur, is under threat due to deforestation and loss of its natural habitat. The awareness about Malaysia Native wildlife problem should be raised and focused by Malaysian. So, this project will select 3 main wildlife as the main wildlife to rescues which is Orang Utan, Malayan Tapir and Malayan Flying Lemur. This is to develop a serious game called “Born” which focuses on raising awareness of Malaysia Native Wildlife extinction issues among students. The objective of this project is to study the game mechanic of the developed 2D platform serious game, develop a serious game for protecting Malaysia Native Wildlife and evaluate the functionality of the developed game. This project is developed by using Rapid Application Development (RAD), which is intended for individual developers who need to complete the whole projects in short period of time. The game is developed by using Unity 2D engine, Photoshop, Clip Studio Paint and Medibang. The final product is deployed on PC platform and it will available on Itch.io, a platform to upload and download the game for free.